Analisis Penggunaan Teori SWOT Pada Showroom Mobil Bekas Di UD. ALDO MOTOR Kec Waru Sidoarjo - Amanda Eka Saputri; Gilang Ramadani; Muhammad Yasin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
There are many cases of MSMEs in Indonesia that are not precise in carrying out business strategies due to a lack of knowledge and understanding in building the business. Therefore, a business can achieve its target if the implementation of a business strategy is the driving force for increasing the income of a business. So, this study aims to analyze the strategy of an MSMEs in Waru sub-district, Sidoarjo regency with a descriptive qualitative research method and data collection using interviews, observation or observation, and data analysis was also carried out to strengthen the data needed by researchers. This study uses the SWOT theory to determine the Strengths, Weaknesses, Opportunities, Threats at UD. ALDO MOTOR. The results of this study indicate that there are problems at UD. ALDO MOTOR is a location that is not strategic because it is not right on the main highway so consumers who want to go to the showroom location have a little difficulty with the bookkeeping at UD. ALDO MOTOR is still a mess because the owner still doesn't understand and understand.